Pengukuran Kualitas Butir Soal Pilihan Ganda Untuk Meningkatkan Evaluasi Pembelajaran Pengantar Industri Migas - Eka Megawati; Meita Rezki Vegatama; Nusrotus Sa’idah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Evaluating the quality of test instruments is an important step in ensuring the acceptability and accuracy of measuring student learning outcomes. This study aims to analyze the quality of 50 multiple-choice questions in the Introduction to the Oil and Gas Industry course in terms of validity, reliability, difficulty level, and discriminatory power. The method used is quantitative item analysis with a descriptive and inferential statistical approach based on the results of validity tests, reliability using Cronbach's Alpha, difficulty level, and discriminatory power. The analysis results show that most of the items are valid. The reliability test obtained a Cronbach's Alpha value of 0.88 which is included in the high category, indicating good internal consistency of the instrument. The level of difficulty of the questions is predominantly in the medium category, while the discriminatory power is mostly in the good category. However, several items were still found to be invalid and have low discriminatory power so that they need to be revised or removed. Overall, the test instrument in the Introduction to the Oil and Gas Industry course can be categorized as good quality and suitable for use with improvements to certain items.